Assessment Of Pond Water Quality Of Thakurgaon Sadar Upazila For Fish Production - Islam, MJ; Akter, A; Kamrujjaman, M; Siddiqa, A; Aktar, S (International Journal of Agricultural Research, Innovation and Technology, 2013)
During dry season, physico-chemical properties of waters from 30 ponds of Thakugaon Sadar Upazila, Thakurgaon, Bangladesh were analyzed for its quality and suitability for aquaculture. The variation in the physico-chemical parameters of the aquaculture ponds above or below standard values has potential effects on the health and productivity of aquaculture. Overall, we found that the pond water were acidic to neutral in nature (pH varied from 6.0 to 7.2) and could be suitable for aquaculture. The dissolved oxygen (DO) concentration was suitable for fish production but more DO level should be present for all aquatic life especially for fish production. Chemical oxygen demands (COD) of all pond waters were within the permissible limits for fish production. The temperature values were remained within the standard values in all the aquaculture ponds. Pond water samples contained Ca2+, Mg2+ and Na+ as the dominant cations and HCO3- and Cl- were the dominant anions. All samples were within soft class regarding hardness. Based on Zn2+, Mn2+, Fe3+, SO42-, NO3- and Cl- all pond water samples were within the safe limit for fish production during dry period. Int. J. Agril. Res. Innov. & Tech. 3 (1): 29-34, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16052